Prevalence of Intestinal Parasitic Infestation Among Hearing and Speech Impaired Children of Banke, Nepal - Rai, Maya; Neupane, Ganesh Prasad; Dhami, Dabal Bahadur; Paudel, Thakur Prasad (Journal of Nepalgunj Medical College, 2018)
Introduction: The parasites can cause different gastrointestinal disorders which have great impact on life quality. Hearing and speech impaired children are unable to maintain proper sanitation, making them more prone to intestinal parasitic infection.Aim and Objective: To know the prevalence of various parasitic infestations among hearing and speech impaired Children.Materials and Methods: Stool specimen were collected from 104 hearing and speech impaired children who were living in private rehabilitation school of chisapani village of Banke district Nepal for a period of 5 month from December 2017 to April 2018 and direct wet mount was prepared using normal saline (0.9%) and Lugol's iodine (0.5%). The wet mount was observed under microscope for parasites.Results: Among 104 individuals intestinal parasites were seen in 25.96 % of students. Giardia lamblia (37.04%) was the most common parasite followed by Ascaris lumbricoides (18.52%) and Entamoeba histolytica (14.82%).Conclusion: The study shows that although the speech and hearing impaired children are more prone to parasitic infection, the prevalence is same as normal people. Giardia lamblia, Ascaris lumbricoides and Entamoeba histolytica were the common parasites. Prompt diagnosis and treatment of infected children should be undertaken.